2017
DOI: 10.1016/j.sleep.2017.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of snoring, rather than apnea–hypopnea index, predicts both cognitive and behavioral problems in young children

Abstract: Objective Primary snoring (PS) and obstructive sleep apnea (OSA) not only affect the quality of sleep in a large number of young children, but have also been repeatedly associated with a variety of behavioral and cognitive problems. However, little is known about the potentially differing relationships of behavioral and cognitive pathology within the sleep disordered breathing (SDB) spectrum. Method This study examined data from an enriched for snoring community sample of 631 children aged between 4 and 10 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 67 publications
2
83
0
1
Order By: Relevance
“…Although the clinical relevance of detecting snoring, especially less‐frequent snoring, remains to be established, the present study has shown that snoring 1–6 nights a week is associated with increased airway symptoms, and the systemic symptoms of hypertension, diabetes and heart disease. This finding suggests that less‐frequent snoring might be related to physical and mental disorders, as was observed in the associations between snoring 1–2 nights per week and a higher prevalence of impaired cognitive function or enuresis in children …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although the clinical relevance of detecting snoring, especially less‐frequent snoring, remains to be established, the present study has shown that snoring 1–6 nights a week is associated with increased airway symptoms, and the systemic symptoms of hypertension, diabetes and heart disease. This finding suggests that less‐frequent snoring might be related to physical and mental disorders, as was observed in the associations between snoring 1–2 nights per week and a higher prevalence of impaired cognitive function or enuresis in children …”
Section: Discussionmentioning
confidence: 53%
“…This finding suggests that less-frequent snoring might be related to physical and mental disorders, as was observed in the associations between snoring 1-2 nights per week and a higher prevalence of impaired cognitive function or enuresis in children. 31,32 This study had several limitations. First, Japan Gerontological Evaluation Study 2013 was based on a postal self-reported questionnaire and not on face-to-face interviews or diagnoses by clinical specialists.…”
Section: Discussionmentioning
confidence: 96%
“…In other words, if we consider NE as a morbid consequence of SDB, then even the mildest forms of SDB are sufficient to increase the risk of such morbidity. These findings are reminiscent of recent studies showing that snoring once a week was associated with cognitive and behavioral impairments, the latter being assessed with standardized test batteries . Furthermore, Smith et al also reported that alterations in behavioral measures reached a plateau in the children who snored ≥2 nights per week, while cognitive function was increasingly likely to be impaired as the snoring frequency increased.…”
Section: Discussionmentioning
confidence: 61%
“…These findings are reminiscent of recent studies showing that snoring once a week was associated with cognitive and behavioral impairments, the latter being assessed with standardized test batteries . Furthermore, Smith et al also reported that alterations in behavioral measures reached a plateau in the children who snored ≥2 nights per week, while cognitive function was increasingly likely to be impaired as the snoring frequency increased. Thus, although causal inferences cannot be drawn from our results, we would propose that NE is a significant and direct end‐organ morbidity of SDB in children, in which dose‐dependency relationships are detectable.…”
Section: Discussionmentioning
confidence: 61%
“…The number of apnea and hypopnea episodes per hour during a polysomnographic test is reported as the apnea‐hypoxemia index (AHI), considered to be the gold standard approach to diagnose OSA and assess the severity of sleep disordered breathing (SDB) 12, 17. The AHI definition classifies the threshold values of the estimated prevalence and severity distribution of OSA as normal (<5), mild (5 ≤ AHI < 15), moderate (15 ≤ AHI < 30) and severe (AHI > 30) 12, 18…”
Section: Introductionmentioning
confidence: 99%